Development and initial evaluation of a measure of positive beliefs about dissociative experiences. Issue 3 (27th May 2021) - Marsden, Lena; Longden, Eleanor; Parry, Sarah; Morrison, Anthony; Varese, Filippo
ABSTRACT: Theoretical models and qualitative research suggest that dissociation can be functional in some circumstances, despite being a cause of concern for many. This is the first study that evaluates a novel questionnaire on positive appraisals of dissociation (the Positive Beliefs about Dissociation Questionnaire; PBD-Q), and its link with dissociation frequency and related distress. Development of items was based on lived experience expertise within the research team and qualitative findings. Items were refined through cognitive interviewing with people with lived experience of dissociation prior to deployment using an online survey. A sample of 228 participants scoring >10 on the Dissociative Experiences Scale (DES-II) completed a battery of measures comprising the PBD-Q and a previously developed measure of negative beliefs of dissociation. Exploratory factor analysis revealed three factors: positive beliefs about emotion management, positive beliefs about self-expression, and positive beliefs about maintaining social image. Within this particular sample the PBD-Q showed excellent internal consistency, face validity, convergent validity, and test–retest reliability. Higher scores on the PBD-Q were significantly related to higher frequencies of dissociative experiences as well as dissociation-related distress. The factor structure remained stable when the analyses were restricted to individuals scoring >30 on the DES-II. In conclusion, our findings indicate that positive beliefs about dissociation can be reliably and validly measured in adults who experience levels of dissociation that are higher than the general population. These beliefs could be involved in the maintenance of dissociation and represent promising targets for future research, clinical assessment, and treatment.